The Gender Gap in Agricultural Productivity : The Role of Market Imperfections - Palacios-López, Amparo; López, Ramón (Taylor and Francis, 2015)
This paper hypothesises that labour and credit market imperfections – by discouraging off-farm income-generating activities and restricting access to inputs, respectively – affect female farm productivity more deeply than male productivity. The paper develops a theoretical model, which decomposes the contribution of various market imperfections to the gender productivity gap. Empirically we show that agricultural labour productivity is, on average, 44 per cent lower on female-headed plots than on those managed by male heads. 34 per cent of this gap is explained by differences in labour market access and 29 per cent by differences in credit access.